MARKO CHEREMSHYNA’S MANIÈRE D’ÊTRE IN THE LITERARY IN CRITICAL RECEPTION OF DMYTRO DONTSOV - Nabytovych, Ihor (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2024)
The article examines Dmytro Dontsov’s literary reception of the work of Marko Cheremshyna (Ivan Semaniuk), the search for his manière d’être. The reception of Marko Cheremshyna’s work in Ukrainian literary studies of the first half of the 20th century can be a significant example of mastering and presenting the writer’s work from the perspective of discourse strategies and descriptive practices of certain literary trends of that period. Each of the literary ideological and ideas-aesthetic directions of that period – national-ethnographical, neoclassical and Marxist-Leninist – has a field of discourses about Cheremshyna’s work in literary studies. The nation-centric discourse of Dmytro Dontsov is somewhat less mastered and explored in the creative world of Marko Cheremshyna. Using the example of the analysis of the reception of Marko Cheremshyna’s prose, it is proved that the ideas of the national-ethnographical literary discourse are picked up by Marxo-Leninism, vulgarizing his ideas of the writer’s search for national identity and reducing them to class confrontation. At the same time, neoclassical discourse and nationalist discourse, which are formed almost simultaneously, in many aspects have many common artistic origins and narrative, methodological strategies of literary studies.